A multivariate spatial analysis of a Thule dwelling from Assuukaaq Island, northern Quebec - Farid, Emma Louise (University of Calgary, 1999)
UARC Copyright waiver included: y Bibliography: p. 153-171 http://dx.doi.org/10.11575/PRISM/1783 http://dx.doi.org/10.11575/PRISM/21936